IS CADAVER STILL NEEDED IN MEDICAL EDUCATION? - Muhammad Mansyur Romi; Nur Arfian; Dwi Cahyani Ratna Sari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: Medical education has been developing very rapidly. Cadavers, which can serve as very important learning resources, need special concern for their availability and utility.Methods: This narrative review is based on related articles freely downloaded which discuss the role and availability of cadavers worldwide. The recent Indonesian condition with Universitas Gadjah Mada as a case will be described.Results: Cadavers play important roles in several aspects, from bioethics and behavioral development until clinical skills, in basic education and especially in postgraduate and advance clinical training. The availability of cadavers has declined significantly, and as a result, the impacts must be considered. Most cadavers are unidentified bodies, eventhough presently a body donation program is recommended as the alternative source.Conclusion: Currently in Indonesia, timely participation is needed from various stakeholders to support effective and efficient cadaver availability and utility. Additional learning resources are needed to be developed in order to assure quality improvement of medical education.Keywords: cadaver, medical education, bioethics, unidentified bodies, body donation.